COVID-19 and the hearth - Del-Carpio-Muñoz, Freddy (2021)
The coronavirus disease 2019 (COVID-19), in less than one year, has been causing havoc to the world's public health. With more than 35 million reported cases, more than 1 million fatalities worldwide, and the persistently growing number of infections; a resolution to this health crisis is not visualized in the short- or mid-term. Besides the pulmonary complications, the medical community has called attention to the cardiac compromise. In this brief article we review the most important aspects of COVID-19 related myocardial injury, the possible mechanisms, the prognostic implications and the possible persistent myocardial injury and physical activity restrictions in patients who recovered from the infection.